Fuzzy Logic-Based Performance Enhancement of FSO Systems Under Adverse Weather Conditions - Hassan Yousif Ahmed; Medien Zeghid; Akhtar Nawaz Khan; Somia A. Abd El-Mottaleb (Photonics)
In this paper, we propose an application of fuzzy logic control (FLC) to improve the system performance of free-space optics (FSO) networks using the optical code-division multiple-access (OCDMA) technique. The primary objective is to dynamically adjust the bit error rate (BER) threshold at the receiver based on weather conditions (i.e., rain and fog) and the propagation distance (which significantly affects the received power). The FLC module at the receiver integrates and processes these variables to optimize the BER threshold. The FLC module operates through an algorithm comprising eight well-defined steps, ensuring robust and adaptive control of the BER. Simulation results show that the FSO-FLC-based system has significant advantages over traditional approaches. For instance, under heavy rain conditions, the FSO-FLC system supports 12 users compared to a traditional system, which supports 7 users without FLC over a distance of 2.8 km with BER <semantics>10−9</semantics>. Similarly, under heavy fog conditions, the FSO-FLC system can support 22 users compared to a traditional system, which supports 18 users without FLC over a distance of 0.5 km with equal BER. These values show that the performance of FSO under weather conditions significantly improves when using the proposed approach. The computational efficiency and real-time feasibility of the FSO-FLC are also analyzed. The complexity of the FLC is O(1), indicating that the execution time remains constant regardless of input size. An Intel Core i7-1165G7 (2.80 GHz) using MATLAB’s fuzzy logic toolbox is used for all experiments. Results show that the proposed FLC executes up to 4 ms per decision cycle, which ensures real-time adaptability for practical FSO communication systems.